Seismic Performance of Prestressed Prefabricated Concrete Frames with Mechanical Connection Steel Bars - Yi Wang; Chennan Liu; Chuanzhi Sun; Ashraf Ashour; Shan Yao; Laiyong Luo; Wenjie Ge (Buildings)
Seismic resilience is a critical concern in the development of prefabricated concrete structures. This study investigates the seismic performance of prestressed prefabricated concrete frames with mechanically connected steel bars through both experiment and finite element simulations using ABAQUS. The research aimed to evaluate the influence of prestressed and mechanical connections on structural stiffness, energy dissipation and failure mechanisms, and a restoring force model was developed based on the experimental and numerical results to provide a theoretical basis for seismic design. The parametric analysis based on the verified numerical model shows that the pretension can significantly enhance the bearing capacity, stiffness and deformation recovery ability of the prefabricated concrete frames. The peak load increased by 30.8%, the initial stiffness improved by 17.4%, the ductility coefficient reached 2.82, the residual deformation rate reduced by 40.7%, the emergence and development of cracks delayed, and the crack width reduced. Improving the effective prestress in a certain range can improve the bearing capacity and initial stiffness of the frame. Increasing the strength of concrete and the ratio of the longitudinal reinforcement of beam and column can effectively enhance the bearing capacity of the frame. With the increase of axial compression ratio in a certain range, the bearing capacity and initial stiffness of the frame increase significantly, but the ductility decreases. Based on the hysteresis curve and skeleton curve tested, the skeleton curve model and stiffness degradation law of the prestressed prefabricated concrete frames reinforced with mechanical connection steel bars were fitted, and the restoring force model was established. The predicted value was in good agreement with the experimental value, illustrating the validity of the model developed. These results offer valuable insights for optimizing the seismic design of prefabricated concrete frames, ensuring a balance between strength, stiffness, and ductility in earthquake-resistant structures.